Comparison of the Method of Learning Based on Problems (ABP) Versus a Traditional Method Applied to the Pharmaceutical Attention (P A) - Delgado P., Gladys (2008)
To apply the PBl method oriented to PH C to measure the efficiency of this form of training in the learning of the critical stages of pharmacotherapy follow-up, such as the determinaban of DRPs and the formulation c>f the therapeutic plan. In the control group (n = 32 Ph Ch) only 5 participants (16%) correctly identify health problems, 26 (81%) correctly identifies the DRP, in the intervention group (n = 14 Ph Ch) all do it properly. On the literature review, 47% of participants believe that this is important to determine DRP of the group control, whereas 64% does it en the group with intervention. Regarding the formulation of the therapeutic drug plan, 50% of the control group and 71% of the group with intervcntion, identify like important the exposition of aims. Evaluating the resulted averages obtained like puntaje or total qualification on a maximum of 20 points obtained a value t (95%) of 7.64 (p